Impact of Land Use Types on Soil Physico-Chemical Properties, Microbial Communities, and Their Fungistatic Effects - Giuseppina Iacomino; Mohamed Idbella; Salvatore Gaglione; Ahmed M. Abd-ElGawad; Giuliano Bonanomi (Soil Systems)
Soilborne plant pathogens significantly impact agroecosystem productivity, emphasizing the need for effective control methods to ensure sustainable agriculture. Soil fungistasis, the soil’s ability to inhibit fungal spore germination under optimal conditions, is pivotal for biological control. This study explores soil fungistasis variability across land-use intensities, spanning deciduous and evergreen forests, grasslands, shrublands, and horticultural cultivations in both open fields and greenhouses. Soil characterization encompassed organic matter, pH, total nitrogen, C/N ratio, key cations (Ca2+, Mg2+, K+, Na+), enzymatic activities, microbial biomass, and soil microbiota analyzed through high-throughput sequencing of 16s rRNA genes. Fungistasis was evaluated against the pathogenic fungi Botrytis cinerea and the beneficial microbe Trichoderma harzianum. Fungistasis exhibited similar trends across the two fungi. Specifically, the application of glucose to soil temporarily annulled soil fungistasis for both B. cinerea and T. harzianum. In fact, a substantial fungal growth, i.e., fungistasis relief, was observed immediately (48 h) after the pulse application with glucose. In all cases, the fungistasis relief was proportional to the glucose application rate, i.e., fungal growth was higher when the concentration of glucose was higher. However, the intensity of fungistasis relief largely varied across soil types. Our principal component analysis (PCA) demonstrated that the growth of both Trichoderma and Botrytis fungi was positively and significantly correlated with organic carbon content, total nitrogen, iron, magnesium, calcium, and sodium while negatively correlated with fluorescein diacetate (FDA) hydrolysis. Additionally, bacterial diversity and composition across different ecosystems exhibited a positive correlation with FDA hydrolysis and a negative correlation with phosphoric anhydride and soil pH. Analysis of bacterial microbiomes revealed significant differences along the land use intensity gradient, with higher fungistasis in soils dominated by Pseudoarthrobacter. Soils under intensive horticultural cultivation exhibited a prevalence of Acidobacteria and Cyanobacteria, along with reduced fungistasis. This study sheds light on soil fungistasis variability in diverse ecosystems, underscoring the roles of soil texture rather than soil organic matter and microbial biomass to explain the variability of fungistasis across landscapes.